Penguatan Branding dan Pemasaran Produk Lokal UMKM Sungai Penuh - Anggia Ayu Lestari; Melifia Liantifa; Jeke Jufitra (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Micro, small, and medium enterprises (MSMEs) in the culinary sector in Sungai Penuh City face major challenges in branding and digital marketing capabilities. This community service activity aims to improve MSME actors’ ability to build brand identity and expand marketing reach through digital marketing strategies. The methods used include training, mentoring, and expert lectures focusing on product branding, packaging design, and the use of social media and marketplaces. The results show an increase in MSME understanding of branding concepts, improved ability to create product visual identity, and better utilization of digital media for marketing purposes. This activity contributes to enhancing the competitiveness of local culinary products in broader markets.